The Influence Of Work Environment And Compensation On Employees’ Retention At PT. Cemindo Gemilang Bengkulu City - Ifan Caesar Ramadhan; Neri Susanti; Nirta Vera Yustanti (Penerbit Jurnal Indonesia, 2023)
The aim of the research is to find out the influence of the work environment and compensation on employee retention at PT. Cemindo Gemilang Bengkulu City. This type of research is correlational, namely research to determine the influence and level of influence between two or more variables without any attempt to influence these variables. The sample in this study used a total sampling technique, where the entire population was sampled, amounting to 42 people. Based on the research results, there is an influence of the work environment (X1) on employee retention (Y) of PT. Chemindo Gemilang with a tsig value < α (0.001 ttable (2.571> 1.68195), thus Ho is rejected and Ha is accepted. From the significance value obtained, variable X1 has a negative effect on employee retention (Y). There is an influence of compensation (X2) on employee retention (Y) of PT. Chemindo Gemilang with a tsig value < α (0.004 ttable (2.571> 1.68195), thus Ho is rejected and Ha is accepted. From the significance value obtained, the variable X2 has a negative effect on employee retention (Y). The value of Fsig < α 0.05 and Fcount > F table (16.373>2.83) so it can be concluded that together the independent variables have a negative effect on the dependent variable